2021
DOI: 10.3390/ani11010155
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Parasitism in Miranda Donkeys: Epidemiology and Selective Control of Strongyles Infection in the Northeast of Portugal

Abstract: In Portugal, equine parasitism in pasture animals is characterized by high parasitic burden and high helminthic biodiversity; both factors are potentially pathogenic for their hosts. The decrease in the number of donkeys over the last years in Portugal, their importance in rural lowland and mountain ecosystems and pastures and the scarce information regarding their parasitism led to this research, which aimed to evaluate the parasitological status of a Miranda donkey breed population, a native breed mainly loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 56 publications
2
4
0
Order By: Relevance
“…Regardless, the disease status seemed to have no impact on the infective nematode species, since strongyle-type eggs and cyathostomin larvae were highly abundant and prevalent in both groups. This reflects the reported trends for helminth infections in equids in Portugal [ 22 , 23 , 43 ].…”
Section: Discussionsupporting
confidence: 85%
“…Regardless, the disease status seemed to have no impact on the infective nematode species, since strongyle-type eggs and cyathostomin larvae were highly abundant and prevalent in both groups. This reflects the reported trends for helminth infections in equids in Portugal [ 22 , 23 , 43 ].…”
Section: Discussionsupporting
confidence: 85%
“…The donkey population has been decreasing since 1970 but lately this trend has reversed, and it is estimated that the donkey population is 4.3 million globally [17]. In Europe, donkeys are mainly found in Portugal, Spain, Italy and Greece.…”
Section: Introductionmentioning
confidence: 99%
“…ivermectin (IVM), abamectin, moxidectin (MOX)]. It has been reported that the prevalence of S. vulgaris may increase if selective therapy is adopted in horses (Tydén et al ., 2019 ) and in donkeys (Sousa et al ., 2021 ).…”
Section: Helminth Infections In Horses and Donkeys: Head To Head!mentioning
confidence: 99%
“…Helminth infections in horses and donkeys: head to head! Horses and donkeys not only share similar parasites but also hold high helminth biodiversity (Gianfaldoni et al, 2020;Sousa et al, 2021). Both species can act as reservoirs for each other; however, in donkeys parasitized with a high helminth burden, clinical signs such as diarrhoea and poor body condition are less common than in horses (Matthews and Burden, 2013).…”
Section: Introduction: Early Data and Similaritiesmentioning
confidence: 99%